The capability of heterogeneous γδ T cells in cancer treatment - Yan, Wenyi; Dunmall, Louisa S. Chard; Lemoine, Nicholas R.; Wang, Yaohe; Wang, Yafeng; Wang, Pengju (Frontiers in Immunology, 2023)
γδ T cells, a specialized subset of T lymphocytes, have garnered significant attention within the realm of cancer immunotherapy. Operating at the nexus between adaptive and innate immunological paradigms, these cells showcase a profound tumor discernment repertoire, hinting at novel immunotherapeutic strategies. Significantly, these cells possess the capability to directly identify and eliminate tumor cells without reliance on HLA-antigen presentation. Furthermore, γδ T cells have the faculty to present tumor antigens to αβ T cells, amplifying their anti-tumoral efficacy.Within the diverse and heterogeneous subpopulations of γδ T cells, distinct immune functionalities emerge, manifesting either anti-tumor or pro-tumor roles within the tumor microenvironment. Grasping and strategically harnessing these heterogeneous γδ T cell cohorts is pivotal to their integration in tumor-specific immunotherapeutic modalities. The aim of this review is to describe the heterogeneity of the γδ T cell lineage and the functional plasticity it generates in the treatment of malignant tumors. This review endeavors to elucidate the intricate heterogeneity inherent to the γδ T cell lineage, the consequential functional dynamics in combating malignancies, the latest advancements from clinical trials, and the evolving landscape of γδ T cell-based oncological interventions, while addressing the challenges impeding the field.